Boro como atenuador dos efeitos de déficit hídrico em soja (Glycine max L.) - Souza Júnior, Paulo César de (2021)
The lack of water in certain intensity and duration can cause water stress in different plant species, being the main abiotic stress that limits the growth, development and yield of crops. In this scenario, some compounds based on macro and micronutrients have been promising for increasing plant tolerance to different abiotic stresses. The overall objective of this study was to evaluate the feasibility of foliar B supplementation to mitigate the deleterious effects caused by low soil water availability in soybean (Glycine max L.). We tested the hypothesis that the foliar application of the micronutrient boron (B) can attenuate the effects caused by water deficit in soybean plants, by stimulating the accumulation of osmoprotectors, the enzymatic antioxidant defense system and the maintenance of root growth. The experiment was conducted in an entirely randomized design, under 2x4 factorial scheme, with 5 repetitions. The variation factors were two water conditions (irrigated and deficit water) and four doses/sources of B (Water; B-MEA 150 mg B L-1; B-MEA 300 mg B L-1 and H3BO3 150 mg B L-1) totaling 8 treatments. The evaluations occurred in three moments, according to the level of imposition of the water conditions: maximum stress, rehydration and final yield. Water stress increased in hydrogen peroxide and malondialdehyde levels, the activity of the enzymatic antioxidant system, and was a limiting factor for growth. After rehydration, a rapid resumption of growth could be observed through net CO2 assimilation of the entire plant. There was a 42% increase in root dry mass in plants that were subjected to water deficit and received B compared to the control, with water application only (MOCK). In relation to production, B supplementation positively influenced pod dry mass, harvest index, and the number of grains and pods per plant, especially in plants under water deficit. Foliar B supplementation was able to mitigate the damage caused by low water availability in soybean